IMPLEMENTASI PROGRAM PENDIDIKAN GURU PENGGERAK (PGP) DI KABUPATEN SUMEDANG - Sudrajat, Arip Rahman; Ramdhani, Adithya Kusuma; Nurpalah, Dadan; Soleha, Imelda Amanda; Meilani, Rani; Sanindah (JRPA - Journal of Regional Public Administration, 2024)
The purpose of this research is to find out, obtain objective data and information about the Implementation of the Pendidikan Guru Penggerak (PGP) Program in Sumedang District. The method used in this research is descriptive analysis with a qualitative approach. The research determination technique is purposive sampling. The research informants include the Head of the PGP program committee, the Finance Division of the PGP program committee, and the Program Division of the PGP program committee. The data collection techniques used are literature review and field studies consisting of observation, interviews and documentation. While the data processing procedures in this study are data reduction, data display, and data conclution drawing/verification. Based on the research results, it can be described that the implementation of the PGP program has gone well but is still not optimal due to several obstacles, including factors such as poor information, lack of teacher motivation and understanding regarding the PGP program, and restrictions on the quota of participants who take part in each program. class, which causes several members who have graduated to have to "park" first because of the limited quota. The suggestions for this PGP program are establishing collaboration, using multi-channel communication, and holding forums or regular meetings to share experiences and inspiration between teachers.